(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
This study aims to determine the metal content of cadmium (Cd) in mussel (Corbicula sp.) in Palembang Musi River. The sampling method was purposive sampling method. Based on the source of metal contamination of cadmium (Cd) in the Musi River in Palembang administrative region, the location of the study were divided into eight stations. The results showed the average metal concentrations of cadmium (Cd) in mussel tissue (Corbicula sp.) of 0.6801 mg / kg with a range of concentrations between 0.4320 mg / kg - 0.9470 mg / kg with the highest concentration in the area Pulokerto and lowest in the shipyard area of PT. Mariana Bahagia. Cadmium metal concentrations in mussel tissue (Corbicula sp.) is still under No. SNI. 7387 the year 2009 is equal to 1.0 mg / kg. Key words: cadmium, mussels, Musi River